1999
DOI: 10.5271/sjweh.481
|View full text |Cite
|
Sign up to set email alerts
|

New avenues in research on musculoskeletal disorders

Abstract: Viikari-Juntura E, Riihimaki H. New avenues in research on musculoskeletal disorders. Scand J Work Environ Health 1999;25(6, special issue):564-568. Recent reviews on musculoskeletal disorders have clearly pointed out the need for more good-quality original research. Both symptom-based and objective outcome assessment methods should be improved. A variety of methods exists to assess exposure for short-term outcomes, whereas exposure assessment strategies for outcomes with long induction times should be develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The limitations of available diagnostic technologies for MSDs have been discussed by others [41,85]. Diagnostic criteria are not standardized and are often inconsistent from one examiner to another, even though there are consensus documents for several upper extremity MSDs [28,62,75].…”
Section: Msd Case Definitionsmentioning
confidence: 99%
“…The limitations of available diagnostic technologies for MSDs have been discussed by others [41,85]. Diagnostic criteria are not standardized and are often inconsistent from one examiner to another, even though there are consensus documents for several upper extremity MSDs [28,62,75].…”
Section: Msd Case Definitionsmentioning
confidence: 99%
“…The role of the psychosocial factors at work has been much debated (Bongers et al 1993;Viikari-Juntura and Riihima¨ki 1999), and the role of psychosocial factors in childhood has also been the object of research (Viikari-Juntura et al 1991). However, many studies have focused either on physical factors, with little or no effort to quantify psychosocial exposures, or on psychosocial factors, without adjusting for physical exposures.…”
Section: Introductionmentioning
confidence: 98%
“…It is suggested that new research paradigms are needed to study dynamic processes associated with these factors (40,41). The monitoring of tension can be a useful intermediate response variable in this respect.…”
Section: Tension As State or Traitmentioning
confidence: 99%